Evaluation and selection of rapeseed (Brassica napus L.) mutants for higher seed yield - Malek, Md. Abdul (WFL Publisher, 2014)
A field experiment was conducted to investigate some morpho-physiological characters, yield attributes and yield of three rapeseed mutants along with mother variety. Results revealed that LAI and AGR increased till 65 days after sowing (DAS) followed by a decline at later growth stages whereas RGR decreased with age of the plants. Two plant characters such as LAI and AGR contributed to the superior TDM production. Results indicated that a high yielding rapeseed genotype should possess larger LAI, higher TDM production ability, superior AGR at all growth stages, superior biochemical parameters which result in superior yield components and seed yield.